Muscle quality responses to short-term resistance training volume in older adults: an exploratory clinical trial - Knowles, Kevan S.; Banks, Logan A.; Cabrera, Vanessa C.; Wilkinson, Wyatt; Pantoja, Adrian J.; Thomas, Isabella G.; Parsowith, Emily J.; Beausejour, Jonathan P.; Norte, Grant; Stout, Jeffrey R.; Stock, Matt S. (Frontiers in Aging, 2025)
Age-related strength loss is more strongly tied to reduced muscle quality than muscle mass. Echo intensity (EI) measured by B-mode ultrasonography is a common marker of intramuscular adiposity and fibrous tissue. Although high-intensity resistance training is effective, the added value of higher training volumes on muscle quality and strength in older adults remains unclear. Moreover, previous studies examining EI changes following resistance training have provided mixed results. To resolve these issues, this exploratory study compared the effects of different resistance training volumes on muscle quality, size, and strength among older adults. Twenty-five older adults (14 males, 11 females; mean ± SD age = 70 ± 7 years) were randomized to moderate volume (n = 14; 2 sets per exercise; 12 sets per week) or high volume (n = 11; 6 sets per exercise; 36 sets per week) training groups. Cohort-specific test-retest reliability statistics were determined prior to the intervention. Participants trained twice weekly, performing knee extension, trap-bar deadlift, and leg press at 85% of one-repetition maximum (1RM). Pre- and post-intervention assessments included ultrasonographic measures of the vastus lateralis (VL) and rectus femoris (RF), leg lean mass, knee extension 1RM, isometric and isokinetic quadriceps strength, and functional tests. The results indicated no significant group × time interactions with small-to-moderate effect sizes, suggesting that increasing volume three-fold provided no additional benefit. When collapsed across group, improvements were found for VL EI (p = 0.025, ηp2 = 0.200), VL (p = 0.015, ηp2 = 0.232) and RF cross-sectional area (p < 0.001, ηp2 = 0.440), knee extension 1RM (p < 0.001, ηp2 = 0.794), isometric peak torque (p < 0.001, ηp2 = 0.630), and concentric peak torque at 180°/s (p < 0.001, ηp2 = 0.423) and 300°/s (p = 0.009, ηp2 = 0.263). No changes were observed in RF EI, leg lean mass, or functional performance. Despite large mean changes, only <25% of participants exceeded the minimal difference needed to be considered real for any variable. In summary, 6 weeks of moderate volume resistance training elicits meaningful improvements in muscle quality and strength. EI changes were muscle-specific, suggesting heterogeneous adaptations among older adults.